Additive‐Free Organic Solar Cells with Power Conversion Efficiency over 10%. Issue 13 (17th February 2017) - Li, Hui; He, Dan; Mao, Peng; Wei, Yuanzhi; Ding, Liming; Wang, Jizheng
Abstract : Nowadays, solvent additives are widely used in organic solar cells (OSCs) to tune the nano‐morphology of the active blend film and enhance the device performance. With their help, power conversion efficiencies (PCEs) of OSCs have recently stepped over 10%. However, residual additive in the device can induce undesirable morphological change and also accelerate photo‐oxidation degradation of the active blend film. Thereby, their involvements are actually unfavorable for practical applications. Here, a donor material PThBDTP is employed, and PThBDTP:PC71BM based OSCs are fabricated. A PCE of over 10% is achieved without using any additives and film post‐treatments. The device displays a high open‐circuit voltage of 0.977 V, a large short‐circuit current density of 13.49 mA cm ‐2, and a high fill factor of 76.3%. These results represent an important step towards developing high‐efficiency additive‐free OSCs. Abstract : Organic photovoltaic devices with PThBDTP as donor and PC71 BM as acceptor are fabricated, and a power conversion efficiency of over 10% is achieved without resorting to any additives and post treatments.